Analisis Study Komperatif Bubble Sort Dan Selection Sort Pada Algoritma Dan Pemograman Berdasarkan Seleksi Pengurutan - Saputri Saputri; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Technological developments that continue to develop have an influence on the increasing number of data, making it a complicated problem to solve manually. The existence of programming algorithms is a solution in completing the data management process, so that errors do not occur in providing answers to data management results, so that the information provided is more accurate and reliable. Besides that, many sorting algorithms are used as solutions to various problems. The use of this algorithm takes into account various aspects of the problem to be solved. Therefore, first find out the comparison between one algorithm and another algorithm. As in this research, it will explain the comparison of the level of efficiency in the bubble sort and selection sort algorithms, which are investigated based on time efficiency, speed and use. This research was carried out by exploring sources of information from various journals, articles and books. With this research, it can provide a solution in taking the right steps in using the bubble sort and selection sort algorithms, which can be used according to the data management problems to be solved.